The Analysis of Human Resource and Open Space Aspects on Physical Education in Pekalongan City - Ichsandi, Rofa (Universitas Negeri Semarang, 2020)
The purpose of this research is to find out the open space index and the human resource index especially in the field of sports education in terms of the Sport Development Index. This research uses a survey method through a quantitative approach. The research location is in the City of Pekalongan with the research target as West Pekalongan District, North Pekalongan District and East Pekalongan District, and South Pekalongan District. The sampling technique uses total sampling and purposive sampling. The instrument of data collection is done by observation, interview, and documentation. Data collection includes the amount of open space, the total population, the number of physical education teachers from elementary school through high school. Then analyzed using the Sport Development Index of aspects of open space and human resources in order to get conclusions from existing phenomena. The results of the study: 1) the index of physical education human resources is 0.0016 with a low category, 2) the index of outdoor sports is 0.512 with the middle category. The conclusions in this study are the availability of open space and sport human resources, especially in the education sector of Pekalongan City, respectively in the middle and low categories. Suggestions given by researchers are for the government of Pekalongan City to make a program regarding the development and improvement of the quality and quantity of sporting open spaces, sports infrastructure, and human resources, while for the people of Pekalongan City they should use sporting open spaces wisely, responsibly, inviting others to exercise and supporting government programs and adding more self-quality to better human resources.